An auxin maximum in the middle layer controls stamen development and pollen maturation in Arabidopsis. Issue 3 (23rd September 2016) - Cecchetti, Valentina; Celebrin, Daniela; Napoli, Nadia; Ghelli, Roberta; Brunetti, Patrizia; Costantino, Paolo; Cardarelli, Maura
Summary: Here, we investigated the role of auxin distribution in controlling Arabidopsis thaliana late stamen development. We analysed auxin distribution in anthers by monitoring DR5 activity: at different flower developmental stages; inhibiting auxin transport; in the rpk2‐3 and ems1 mutants devoid of middle layer (ML) or tapetum, respectively; and in the auxin biosynthesis yuc6 and perception afb1‐3 mutants. We ran a phenotypic, DR5::GUS and gene expression analysis of yuc6rpk2 and afb1rpk2 double mutants, and of 1‐ N ‐naphthylphthalamic acid (NPA)‐treated flower buds. We show that an auxin maximum, caused by transport from the tapetum, is established in the ML at the inception of late stamen development. rpk2‐3 mutant stamens lacking the ML have an altered auxin distribution with excessive accumulation in adjacent tissues, causing non‐functional pollen grains, indehiscent anthers and reduced filament length; the expression of genes controlling stamen development is also altered in rpk2‐3 as well as in NPA‐treated flower buds. By decreasing auxin biosynthesis or perception in the rpk2‐3 background, we eliminated these developmental and gene expression anomalies. We propose that the auxin maximum in the ML plays a key role in late stamen development, as it ensures correct and coordinated pollen maturation, anther dehiscence and filament elongation.